2006
DOI: 10.1002/chin.200609023
|View full text |Cite
|
Sign up to set email alerts
|

Platinum Monolayer on Nonnoble Metal—Noble Metal Core—Shell Nanoparticle Electrocatalysts for O2 Reduction.

Abstract: Catalysts H 2000Platinum Monolayer on Nonnoble Metal-Noble Metal Core-Shell Nanoparticle Electrocatalysts for O2 Reduction. -New O2 electrocatalysts with a high activity and very low noble metal content consisting of Pt monolayers deposited on the surfaces of carbon-supported non-noble-noble metal core-shell nanoparticles such as Pt/Au/Ni, Pt/Pd/Co, and Pt/Pt/Co are synthesized. The core-shell nanoparticles are formed by impregnation of Vulcan X-72C carbon with mixed solutions of noble and non-noble metal salt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 1 publication
2
63
0
8
Order By: Relevance
“…Higher specific activity (SA) and lower electrochemical surface area (ECSA) or higher Pt utilization in the catalyst with roughly equal ECSA and SA compared to existing catalysts are being explored, for example, using Pt nano-frame and core-shell catalysts, respectively. 8,9 Modeling and simulation are expected to improve the associated issues. [10][11][12] At the same time, non-noble metal catalysts, oxide catalysts, and carbon alloys are being actively researched.…”
Section: Future Fcv Technologies and Infrastructurementioning
confidence: 99%
“…Higher specific activity (SA) and lower electrochemical surface area (ECSA) or higher Pt utilization in the catalyst with roughly equal ECSA and SA compared to existing catalysts are being explored, for example, using Pt nano-frame and core-shell catalysts, respectively. 8,9 Modeling and simulation are expected to improve the associated issues. [10][11][12] At the same time, non-noble metal catalysts, oxide catalysts, and carbon alloys are being actively researched.…”
Section: Future Fcv Technologies and Infrastructurementioning
confidence: 99%
“…On the top of the "volcano" plot is the Pt monolayer on a Pd(111) surface, that is, the most active electrocatalyst among six Pt monolayer-substrate couples, plus the single Pt(111) surface. Our experiments on various Pt monolayer nanoparticles also demonstrated that the variation of the core materials significantly affect the performance of the catalyst [1,[3][4][5][6][7][8][9][10]. Among the Pt ML electrocatalysts we studied for the ORR, the palladium and palladium alloy cores outperform the rest in terms of both activity and stability [6,19].…”
Section: Introductionmentioning
confidence: 66%
“…We summarize the corresponding mass activity and specific activity for the ORR in the inset of Figure 5; 0.25-fold and 0.5-fold enhancements were found, respectively. 3 Co/C. The oxygen-reduction reaction on Pt ML /Pd 3 Co/C attained a Pt mass activity 2∼3-fold that of commercial Pt/C [7].…”
Section: Direct Modification Of the Surface Of The Core [22]mentioning
confidence: 95%
See 2 more Smart Citations